The Relationship between Antiseizure Medications and Sleep Quality Among Epilepsy Patients: A Cross-Sectional Study - Hermawan, Agnes Kartika Sari; Khosama, Herlyani; Jehosua, Seilly Y.; Pertiwi, Junita M.; Karema, Winifred; Wariki, Windy M. V. (International Clinical Neuroscience Journal, 2025)
Background: Poor sleep quality and sleep deprivation provoke epileptic seizures, and sleep-related epilepsy and antiseizure medications (ASMs) affect sleep quality. There is still a limited study exploring the relationship between ASM consumption and the sleep quality of epilepsy patients in developing countries, and this study will be the first one conducted in Indonesia. Methods: This cross-sectional study was conducted from April to June 2023. Subjects were patients aged 18-65 years old, electro-clinically diagnosed with any epilepsy, who had taken at least one ASM. They were seizure-free for at least three months, without a history of anxiety, depression, poor sleep hygiene, or medication adherence. Sleep quality is measured using the Pittsburgh Sleep Quality Index (PSQI). The Fisher-exact test is used to analyze the association. A p-value of <0.05 is considered statistically significant. Results: A total of 64 subjects were included, consisting of 33 males (51.6%), with a median age of 37.8 ± 13.8 years. Poor sleep quality was found in 24 subjects (37.5%) with a median PSQI score of 4.8. Older-generation ASMs (p = 0.023), polytherapy (p = 0.02), and ASM use for less than 1 year (p = 0.003) were significantly associated with poor sleep quality. Conclusions: ASM type, consumption duration, and the number of ASMs are significantly associated with sleep quality. Therefore, routine evaluation of sleep quality and appropriate ASM is recommended for epilepsy patients. Conclusion: The study will be useful while performing surgical procedures around the axis vertebrae to prevent injury to vital structures.